Ca‐Metal Batteries: Hybrid Solid Electrolyte Interphases Enabled Ultralong Life Ca‐Metal Batteries Working at Room Temperature (Adv. Mater. 2/2021). Issue 2 (12th January 2021) - Song, Huawei; Su, Jian; Wang, Chengxin
Abstract : In article number 2006141, Chengxin Wang and co‐workers describe the realization of a stable Ca plating/stripping process for more than 1000 h by a Na/Ca hybrid solid electrolyte interphase (SEI) strategy, which enables an ultralong life for room‐temperature Ca‐metal batteries with high operation voltage up to 4.5 V.